2017
DOI: 10.1021/acs.jpcc.7b03500
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Film and Substrate Structure on Photoelectron Momentum Maps of Coronene Thin Films on Ag(111)

Abstract: Angle-resolved ultraviolet photoelectron spectroscopy (ARUPS) was measured for one-monolayer coronene films deposited on Ag(111). The (kx,ky)-dependent photoelectron momentum maps (PMMs), which were extracted from the ARUPS data by cuts at fixed binding energies, show finely structured patterns for the highest and the second-highest occupied molecular orbitals. While the substructure of the PMM main features is related to the 4 × 4 commensurate film structure, various features with three-fold symmetry imply an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…The orbitals appear similar to those presented by Lüder et al [30]. It should be noted that an experimental analysis of Coronene orbital imaging data is complicated by the degeneracy of HOMO and HOMO-1 and the rotational symmetry of the Coronene molecule, which means that multiple orientations of the molecular orbital can occur simultaneously [31]. This leads to a momentum map in which the rotated contributions of both states are overlapped [32], which breaks the direct Fourier transform relationship between measurement and orbital [33].…”
Section: Sparsity-based Orbital Reconstructionsupporting
confidence: 80%
“…The orbitals appear similar to those presented by Lüder et al [30]. It should be noted that an experimental analysis of Coronene orbital imaging data is complicated by the degeneracy of HOMO and HOMO-1 and the rotational symmetry of the Coronene molecule, which means that multiple orientations of the molecular orbital can occur simultaneously [31]. This leads to a momentum map in which the rotated contributions of both states are overlapped [32], which breaks the direct Fourier transform relationship between measurement and orbital [33].…”
Section: Sparsity-based Orbital Reconstructionsupporting
confidence: 80%
“…In this work, we demonstrate that monolayers of heptacene on Cu(110) behave markedly different compared to all previously studied oligoacene monolayers on coinage metal surfaces, and, to the best of our knowledge, are also dissimilar to any other polycyclic aromatic hydrocarbons adsorbed on metal substrates studied so far. 16 , 26 , 46 , 47 By using STM and combining PT with density functional theory (DFT) calculations, we show that not only the LUMO but also the LUMO + 1 receives charge when heptacene adsorbs face-on and orients along the Cu rows. Conversely, for heptacene still face-on but rotated by 90°, significantly less charge is transferred to the molecule, resulting in only the LUMO being filled and the molecular energy levels being shifted significantly toward the Fermi edge.…”
Section: Introductionmentioning
confidence: 99%
“…It would be advantageous to substantiate this interpretation by simulations of momentum maps for benzene interacting with Pd(110) rather than benzene in the gas phase, that is, by using the wave functions of the benzene/Pd(110) interface as intitial states in the simulation of the photoemission intensity. We have demonstrated that this may indeed improve the agreement with measured momentum maps [60][61][62]. For molecule/metal interfaces with considerable interactions, however, in the present case such simulations are hampered by the fact that the DFT electronic structure has a severe shortcoming.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, the fact that the experimental MM of π 2 appears much sharper in the k [001] -direction than the simulated MM may aslo originate from molecule-substrate interaction. Not only does it lead to energetically broadened molecular resonances, but it also causes an enhanced intermolecular band dispersion which in turn results in substructures and sharper features in constant-binding energy momentum maps [60][61][62].…”
Section: Discussionmentioning
confidence: 99%